THE USE OF CLUSTERING TECHNIQUE IN TEACHING WRITING RECOUNT TEXT - Sholihah, Awalia; Sutapa, Y. Gatot; Susilowati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to find out whether or not the use of clustering technique is effective in teaching writing recount text and if it is effective how effective is the use of clustering technique in teaching writing recount text. In doing this research, the researcher used pre experimental study in one group pretest and posttest design. This research was conducted to the eighth grade students of SMP Islam Bawari Pontianak in Academic Year 2015/2016. The researcher used cluster sampling and the sample of this research was class VIII A. The research found that the technique was effective to enhance students’ recount text writing due to the t-test calculation result which was 10.55. The technique was significantly effective to enhance students’ recount text writing as the result of effect size analysis categorized as high. It was concluded that the technique was able to be used in enhancing students’ recount text writing and the effect was positive. The researcher recommends an English teacher at that school to use this technique as a variation in the teaching process, especially in teaching writing recount text.          Keywords: clustering technique, writing, recount text